The phenomenological model of depression: from methodological challenges to clinical advancements - Frohn, Oskar Otto; Martiny, Kristian Moltke (Frontiers in Psychology, 2023)
In this article our overall aim is to illustrate how phenomenological psychopathology can advance the clinical work on depression. To do so, we start by unfolding the current phenomenological model of depression. We argue that this model faces a methodological challenge, which we define as ‘the challenge of patho-description’. Mental disorders, such as depression, influence how people are able to access and describe their own experiences. This becomes a challenge for phenomenological psychopathology since its methodology is based on people’s ability to describe their own experiences. To deal with this challenge, in the case of depression, we turn to the framework of phenomenological interview. We interview 12 participants (7 women, 5 men, age-range from 29 to 57 years) with moderate and severe depression. From the interview results, we show how phenomenological interview deals with the challenge of patho-description and how patho-description in depression conceals experiential nuances. We unfold these nuances and describe how people with depression pre-reflectively experience a variety of feelings, a type of agency, overly positive self-image, and relations in a hyper-social way. These descriptive nuances not only strengthen the phenomenological model of depression, but they also help advance the clinical work on depression. We firstly illustrate how the descriptive nuances can be added to current manuals and rating scales to advance diagnostic work. Secondly, we illustrate how phenomenological, ‘bottom-up’, and embodied approaches function at the pre-reflective level of experience, and that further effort at this level can help advance therapy for depression.